Communication—Preparation of Highly Monodisperse Ni-Rich Cathode Material for Lithium Ion Batteries. Issue 7 (23rd April 2016) - Lee, Ilbok; Kim, Jaekwang; Han, Seunghee; Park, Jong-Il; Lee, Jae-Myung; Kim, Do-Hyeong; Nam, Sang-Cheol; Yoon, Songhun
Abstract : A novel strategy for preparation of high-Ni LiNix Coy Al1−x−y O2 (NCA) cathode materials for Li-ion batteries (LIBs) was developed by separate addition of bead-milled Al(OH)3 solution to the co-precipitation reaction. Highly homogeneous particles with an average particle size of 5.82 μm were continuously generated for short retention time. This uniform and enhanced particle growth was attributed to limited disturbance of the milled Al(OH)3 particles during co-precipitation. When applied as cathode material, high discharge capacity (198 mAh g −1 ), good initial efficiency (90%), and stable cycleability were achieved, which was attributed to the well-developed crystal structure and monodisperse particles.